Towards a paradigm shift in mosque architecture: coping up with the challenges of contemporary urban context - Asif, Nayeem; Utaberta, Nangkula; Sarram, Arman (Universiti Sains Ismal Malaysia (USIM), 2018)
From its humble beginning at the city of Medina, mosque architecture went through several paradigm shift in terms of planning and design throughout last couple of centuries. However, its fundamental functionality, purpose and appropriateness remains constant. Contemporary urban context has compelled urban planners and architecture to reconsider its planning and implementation, deviating from the usual architectural conventions and faced with the challenge of retaining the integrity of its core values and concept. This paper provides insight on the merits as well as the chal lenges of modern day planning, executing and building of mosque in urban areas by providing a comparative analysis on several mosques from different cities around the world. Qualitative content analysis has been adopted to analyze the compiled literature on selected cases. Outcome of this research's showed that a strong consideration for vertical development should be implemented to serve the needs of a growing population and fast dwindling resources and space. Additionally, results also found that vertical development and practical space usage in harmony with aesthetics and environment to achieve balance of both use and presentation.